Formulation optimization and processing parameter establishment of canned chicken in kacangma herbal soup - Chua , Hun Pin; Aminah Abdullah (Universiti Kebangsaan Malaysia, 2009)
The formulation of chicken in kacangma herbal soup, a traditional delicacy of Sarawak was developed. Processing parameters for the canned product was established. The product was canned and retorted at 121°C in an overpressure retort to achieve commercial sterility. A three-component constrained mixture according to a symmetrical-simplex interior design was used to determine the optimum formulation. Result showed that a mixture with 82% blended ginger, 17% dried kacangma and 1% cornstarch would give a mean sensory score of more than 6.6 for taste, colour, texture, consistency and overall acceptability. Meanwhile, a score above 5.5 was given for aroma. The study showed that the thermal process applied with Fo value of 8.36 is sufficient to produce commercially sterile products.